Immigration and training needs for carers - Manuel Moreno Preciado; Teresa Martín Hernández (Universidad de Alicante, 2012)
Recent studies show a lack of knowledge about the cultures of different ethnic groups in the Spanish setting. It has been largely recognized that several cultural issues such as beliefs, myths, religion, tabooes, habits etc, have an effect in the health-disease-care process. This article shows the need for education programmes in cultural diversity as an essential tool for this new situation, which nowadays has become a challenge for health professionals and particularly for the nursing profession. Studies related to the provision of care to different ethnic groups are identified and analized in this article. A study of the present knowledge of nursing professionals with respect to cultural diversity, through the different educational programmes offered in various institutions, shows the lack of preparation in these professionals to cope with present needs and expectations.